Збірник статей здобувачів вищої освіти другого (магістерського) рівня Навчально-наукового інституту обліку, аналізу та аудиту Університету ДФС України : у 3-х ч. Ч. 1. - ННІ обліку, аналізу та аудиту; Institute of Accounting, Analysis and Audit (Ірпінь, 2019)
У збірнику опубліковано статті здобувачів вищої освіти другого (магістерського) рівня. Видання призначене для молодих вчених, аспірантів, студентів. The collection publishes articles by students of the second (master's) level of higher education. The publication is intended for young scientists, graduate students, and students.
Collection of articles by students of higher education of the second (master's) level of the Educational and Scientific Institute of Accounting, Analysis and Audit of the University of the SFS of Ukraine: in 3 parts, Part 1.
Keywords: обліку, аналіз, аудит, бухгалтерський облік, суб’єкти господарювання; accounting, analysis, audit, accounting, business entities